Influence of Leadership Style, Standard Operating Procedures (SOP), Job Motivation, and Job Satisfaction on the Intention to Leave of Employees at PT. Bintan Bersatu Apparel - Ekawati, Rina; Ratnasari, Sri Langgeng; Susanto, Alpino (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Turnover intention is a problem that many companies still face, especially in labor-intensive industries such as the garment industry. High employee turnover can disrupt operational stability and increase human resource management costs. This research examines how leadership style, standard operating procedures (SOPs), job motivation, and job satisfaction affect employees’ turnover intention. A quantitative method was employed, with data gathered through questionnaires distributed to sewing department workers in a garment manufacturing firm. Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results show that employee psychological factors play a more dominant role in shaping turnover intention than organizational structural factors. Job motivation is the most decisive factor in reducing employees' intention to leave, followed by job satisfaction and leadership style, which act as supporting factors. Meanwhile, SOPs do not play a dominant role in influencing turnover intention because they function more as a mechanism for regulating operational work. These findings indicate that efforts to control turnover intention in labor-intensive industries need to be directed at improving employee motivation and the overall quality of their work experience.